Physical model test on landslide thrust distribution on double-row stabilizing piles - Yuping YAN; Shiguo XIAO (Zhongguo dizhi zaihai yu fangzhi xuebao, 2022)
Distribution pattern of thrust force on double-row stabilizing piles is one of the essential factors for the design of stabilizing piles. For a bedrock-overburden landslide strengthened with double-row stabilizing piles, four sets of laboratory physical model test are conducted considering various rear-row pile configurations. In particular, slip surface softening effect due to heavy rainfall is physically simulated using external water injection and infiltration into the shear band through a special channel. Distribution characteristics of the landslide thrust on the two piles are measured, which is further verified by a numerical simulation method FLAC3D. The test results show that the thrusts on the rear and fore piles present a parabolic distribution pattern, and the location with peak value is relatively close to the slip surface. If the pile location remains unchanged, the peak value of the thrust force behind the rear pile decreases with the increase of its embedded depth and the position with peak value moves upward; while the peak value of the thrust behind the fore pile increases with the embedded depth of the rear pile top, and the position with peak value changes unobviously. The slip surface softening effect does not change the distribution pattern of the thrust forces on piles, but it can increase the thrusts behind the piles; compared with the top and bottom of the piles, the increase of the thrust in the middle part of the piles is relatively larger. The thrust forces on the rear and fore piles under external water injection are about 14.3%~21.4% and 17.9%~24.8% higher than those before the softening action, respectively.